Phosphodiesterases Regulate BAY 41-2272-Induced VASP Phosphorylation in Vascular Smooth Muscle Cells - Adderley, Shaquria P.; Joshi, Chintamani N.; Martin, Danielle N.; Tulis, David A. (Frontiers in Pharmacology, 2012)
BAY 41-2272 (BAY), a stimulator of soluble guanylyl cyclase, increases cyclic nucleotides and inhibits proliferation of vascular smooth muscle cells (VSMCs). In this study, we elucidated mechanisms of action of BAY in its regulation of vasodilator-stimulated phosphoprotein (VASP) with an emphasis on VSMC phosphodiesterases (PDEs). BAY increased phosphorylation of VASPSer239 and VASPSer157, respective indicators of PKG and PKA signaling. In the presence of non-selective PDE inhibition, BAY had no effect on VASPSer239 but inhibited VASPSer157. Selective inhibition of PDE3 or PDE4 attenuated BAY-mediated increases at VASPSer239 and VASPSer157, whereas PDE5 inhibition potentiated increases only at VASPSer157. In comparison, 8Br-cGMP increased VASPSer239 and VASPSer157 which were not affected by selective PDE blockade. In the presence of 8Br-cAMP, inhibition of either PDE4 or PDE5 decreased VASPSer239 and inhibition of PDE3 increased VASPSer239, while inhibition of PDE3 or PDE4 increased and PDE5 inhibition had no effect on VASPSer157. These findings demonstrate that BAY operates via cAMP and cGMP along with regulation by PDEs to phosphorylate VASP in VSM. Given a role for VASP as a critical cytoskeletal protein, these findings provide evidence for BAY as a VASP-selective regulator of VSM growth and a potential therapeutic agent against vasculoproliferative disorders.